Problems With the Presidential Threshold System in Elections - Dochan Mulyana, Fachry (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The presidential threshold system in the general election provides insight into the view of responsibility for improving community rights and political rights guaranteed in the constitution. The presidential threshold continues to be debated among the public, a rule that harms the community and political parties continues to be tested for constitutionality in the Supreme Court. This research aims to examine the relevance and impact of the implementation of the presidential threshold in general elections and examine the decision of the Supreme Court related to the presidential threshold system. This research is legal research with the type of normative legal research. The sources or legal materials used are primary and secondary legal materials with the approach used, namely the approach of legislation. The results of this research show that the presidential threshold rules are not known in other countries that apply the system